2021
DOI: 10.1111/jipb.13111
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome B interacts with SWC6 and ARP6 to regulate H2A.Z deposition and photomorphogensis in Arabidopsis

Abstract: Light serves as a crucial environmental cue which modulates plant growth and development, and which is controlled by multiple photoreceptors including the primary red light photoreceptor, phytochrome B (phyB). The signaling mechanism of phyB involves direct interactions with a group of basic helix‐loop‐helix (bHLH) transcription factors, PHYTOCHROME‐INTERACTING FACTORS (PIFs), and the negative regulators of photomorphogenesis, COP1 and SPAs. H2A.Z is an evolutionarily conserved H2A variant which plays essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…Interestingly, chromatin-remodeling mutants are also hyposensitive to red and far-red light, indicating that the SWR1 complex is also important for phytochrome signaling. Further studies have shown that phytochrome B interacts with SWC6 and ARP6 ( Mao et al, 2021 ; Wei et al, 2021 ).…”
Section: Signal Transduction Through Cryptochrome-interacting Proteinsmentioning
confidence: 99%
“…Interestingly, chromatin-remodeling mutants are also hyposensitive to red and far-red light, indicating that the SWR1 complex is also important for phytochrome signaling. Further studies have shown that phytochrome B interacts with SWC6 and ARP6 ( Mao et al, 2021 ; Wei et al, 2021 ).…”
Section: Signal Transduction Through Cryptochrome-interacting Proteinsmentioning
confidence: 99%
“…After the imbibed seeds were keep at 4°C for 3 days, they were grown on Murashige-Skoog (MS) nutrient medium plus 2% sucrose with 0.8% agar at 22°C under white light. The experiments involving red and far-red light illuminations were described previously ( Wei et al, 2021 ). Light spectra and intensity were measured with a Hand Held spectroradiometer (ASD) and a Li250 quantum photometer (Li-Cor) ( Wei et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The experiments involving red and far-red light illuminations were described previously ( Wei et al, 2021 ). Light spectra and intensity were measured with a Hand Held spectroradiometer (ASD) and a Li250 quantum photometer (Li-Cor) ( Wei et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ACT2 was used as an internal control for quantitative reverse transcription PCR (qRT‐PCR). qRT‐PCR analysis was described previously (Wei et al ., 2021). The primers used are listed in Supporting Information Table S1.…”
Section: Methodsmentioning
confidence: 99%